A critique on the concept of Talaq under the Maldivian family law - Adam, Mohamed Nasheed (Kuliyyah of Laws, International Islamic University Malaysia, 2004)
The alarmingly high rate of divorce in the Maldives is a peril to the very fabric of the Maldivian society. This fact was the incentive that led the Maldivian legislators to promulgate a new family law in the country. This new family law which came into force on the onset of July 2000, makes it obligatory for every husband who wants to divorce his wife to seek prior judicial permission from the Court. In case he fails to abide by this legal provision, he will face a penalty of banishment to an island other than his own and mandatory confinement within this island for a term no more than six months or a fine not exceeding five thousand Rufiyaa. However, this useful penal deterrence is not adequate. Maldives clearly needs more objective measures to be integrated into its family law in order to curb the high rate of divorce. This can only be done if the legislators take into account those classical legal views from Shari 'ah which if successfully implemented, the divorce rate is highly expected to be eventual] y reduced.